(untitled) (Eurasian Journal of Philology Science and Education, 2016)
His article discusses the philosophical ideas about the creation of the world, prevailing in songs-tolgau akyns zhyrau and early twentieth century. Sacred doctrine of creation is addressed to all the descendants of humanity. Therefore, along with the development of the ordinary human history, and akyns zhyrau urged his listeners and attached to the wise laws and mysteries of creation. «What the world created? What lies the main purpose of man coming here? «- Answers to their spiritual quest master jeweler words found in the philosophy of Islam. These motifs Creation heard from the Arch to Atyrau, and through them representatives of the traditional art of singing schools ascribe his audience to the laws of the universe, urging them to take as a perfect example. For understanding and disclosure of the grand goal of the creator of the world and akyns zhyrau society ascribe to deep clean and the origins of Islam. These sources come from the Koran, have strong foundation in the last Messenger of Allah Hadith of the Prophet Muhammad (ғ.s.) and in the writings of Islamic scholars and the heirs of the medieval literary tradition.